Entering university as the first: Understanding first-generation students’ challenges and their coping strategies at Universiti Malaysia Sabah - Charles Ling Leh Kim (2022)
For many first-generation students, higher education act as an important turning point that can help to advance their inherited socioeconomic status. Without university-educated parents, first-generation students often time lack the social capital and cultural capital that are crucial for their integration at university. Therefore, this study explores the challenges faced by first-generation students and the coping strategies they have relied on to overcome them. Semi-structured interviews were conducted virtually with 15 third-year, first-generation students from the Universiti Malaysia Sabah (UMS), a public university in Malaysia. Guided by social capital theory and cultural capital theory, research data were analyzed and coded for themes by using thematic analysis. The research findings demonstrate that first-generation students were academically, socially and financially challenged by the university due to their initial limited understanding of preparation for university. Their past academic experience, family’s socioeconomic background, and parents’ education levels have inevitably placed them in a disadvantaged position at university. However, these students possess positive outlooks that have overshadowed various challenges in their university degree journey. In opposition to the view that first-generation students are less competent to persist at university owing to their socioeconomic backgrounds, the support from their family and peers has significantly motivated them to continue pursuing their dreams. Therefore, it is hoped that the meaningful insights provided in this study can be taken as a valuable reference for universities and schools to better understand this group of students.